Comparison of bee products based on assays of antioxidant capacities - Mishima Satoshi; Shimazawa Masamitsu; Tsuruma Kazuhiro; Nakajima Yoshimi; Hara Hideaki (BMC, 2009)
Abstract Background Bee products (including propolis, royal jelly, and bee pollen) are popular, traditional health foods. We compared antioxidant effects among water and ethanol extracts of Brazilian green propolis (WEP or EEP), its main constituents, water-soluble royal jelly (RJ), and an ethanol extract of bee pollen. Methods The hydrogen peroxide (H2O2)-, superoxide anion (O2·-)-, and hydroxyl radical (HO·)- scavenging capacities of bee products were measured using antioxidant capacity assays that employed the reactive oxygen species (ROS)-sensitive probe 5-(and-6)-chloromethyl-2',7'-dichlorodihydrofluorescein diacetate, acetyl ester (CM-H2DCFDA) or aminophenyl fluorescein (APF). Results The rank order of antioxidant potencies was as follows: WEP > EEP > pollen, but neither RJ nor 10-hydroxy-2-decenoic acid (10-HDA) had any effects. Concerning the main constituents of WEP, the rank order of antioxidant effects was: caffeic acid > artepillin C > drupanin, but neither baccharin nor coumaric acid had any effects. The scavenging effects of caffeic acid were as powerful as those of trolox, but stronger than those of N-acetyl cysteine (NAC) or vitamin C. Conclusion On the basis of the present assays, propolis is the most powerful antioxidant of all the bee product examined, and its effect may be partly due to the various caffeic acids it contains. Pollen, too, exhibited strong antioxidant effects.